Assessment of Thrombectomy versus Combined Thrombolysis and Thrombectomy in Patients with Acute Ischemic Stroke and Medium Vessel Occlusion - Dmytriw, Adam A.; Ghozy, Sherief; Salim, Hamza; Musmar, Basel; Siegler, James E.; Kobeissi, Hassan; Shaikh, Hamza; Khalife, Jane; Abdalkader, Mohamad; Klein, Piers; Nguyen, Thanh N.; Heit, Jeremy J.; et al. (Radiology, 2024)
Background: The combination of intravenous thrombolysis (IVT) with mechanical thrombectomy (MT) may have clinical benefits for patients with medium vessel occlusion. Purpose: To examine whether MT combined with IVT is associated with different outcomes than MT alone in patients with acute ischemic stroke (AIS) and medium vessel occlusion. Materials and Methods: This retrospective study included consecutive adult patients with AIS and medium vessel occlusion treated with MT or MT with IVT at 37 academic centers in North America, Asia, and Europe. Data were collected from September 2017 to July 2021. Propensity score matching was performed to reduce confounding. Univariable and multivariable logistic regression analyses were performed to test the association between the addition of IVT treatment and different functional and safety outcomes. Results: After propensity score matching, 670 patients (median age, 75 years [IQR, 64-82 years]; 356 female) were included in the analysis; 335 underwent MT alone and 335 underwent MT with IVT. Median onset to puncture (350 vs 210 minutes, P <.001) and onset to recanalization (397 vs 273 minutes, P <.001) times were higher in the MT group than the MT with IVT group, respectively. In the univariable regression analysis, the addition of IVT was associated with higher odds of a modified Rankin Scale (mRS) score 0-2 (odds ratio [OR], 1.44; 95% CI: 1.06, 1.96; P =.019); however, this association was not observed in the multivariable analysis (OR, 1.37; 95% CI: 0.99, 1.89; P =.054). In the multivariable analysis, the addition of IVT also showed no evidence of an association with the odds of first-pass effect (OR, 1.27; 95% CI: 0.9, 1.79; P =.17), Thrombolysis in Cerebral Infarction grades 2b-3 (OR, 1.64; 95% CI: 0.99, 2.73; P =.055), mRS scores 0-1 (OR, 1.27; 95% CI: 0.91, 1.76; P =.16), mortality (OR, 0.78; 95% CI: 0.49, 1.24; P =.29), or intracranial hemorrhage (OR, 1.25; 95% CI: 0.88, 1.76; P =.21). Conclusion: Adjunctive IVT may not provide benefit to MT in patients with AIS caused by distal and medium vessel occlusion. (c) RSNA, 2024
Gesehen am 05.02.2026